Pendekatan FMEA dalam Analisa Risiko Perawatan Sistem Bahan Bakar Mesin Induk: Studi Kasus di KM. Sidomulyo - Rizqi Ilmal Yaqin; Zamri Zamri Zamri; Juniawan Preston Siahaan; Yuniar Endri Priharanto; M. Subroto Alirejo; Mega Lazuardi Umar (Jurnal Rekayasa Sistem Industri, 2020)
The fuel system is one of the main engine support systems which is very important in the operation of the KM Sidomulyo main engine. Main engine on ships are operated 24 hours a week or more. The operation main engine needs special treatment of the components on the main engine to prevent failure during operation. Failure Mode and Effect Analysis (FMEA) is a method that can be used to identify the priority scale in maintaining a machine by evaluating the risk of failure that occurs on the machine. This study applies FMEA to determine the priority scale for the maintenance of the KM Sidomulyo main engine fuel system. The results of the identification using FMEA, namely the injector and fuel filter components are components that must be prioritized for maintenance. The Risk Priority Number (RPN) values of the injector and fuel filter components are 192 and 168, respectively. Maintenance priority is based on the component RPN value is above the critical RPN value of the main engine fuel system and includes the priority component on the Pareto diagram. The type of maintenance applied to the injector component is checking dirty fuel which can cause the injector to operate less optimally. While the fuel filter component is cleaning the deposits on the fuel filter cartridge. It is recommended that the inspection of other components be carried out so that the condition of the main engine fuel system has good reliability.